The style of wishing in the poetry of Omar bin Abi Rabia (Journal of Humanities and Social Sciences Research, 2023)
The research aims to study the style of wishing with its original tool (night) inthe poetry of the Umayyad spinning poet Omar bin Abi Rabia Al-Makhzoumi.Neilh, and the style of wishing is one of the methods of requesting constructionthat deviates from its original meaning to other meanings, but the rhetoriciansdid not speak of stating (I wish) a meaning other than wishing because of theantiquity of this tool in the wishing style, which is a sober Arabic style that theArabic language gifted to its speaker so that he could express through it For hisverbal purposes, we presented in this research the poetic evidence that containedthe tool (night) in the poetry of Omar bin Abi Rabia and dealt with it in analysisand detail. And other cases when waiting for the wish to occur, through whichthese feelings and poetic experiences are reflected on the recipient, and he isaffected and attracted towards the experience of the poet expressed.Keywords: